Cerebral Hemodynamics in Normal Aging: Central Artery Stiffness, Wave Reflection, and Pressure Pulsatility. Issue 6 (June 2014) - Tarumi, Takashi; Khan, Muhammad Ayaz; Liu, Jie; Tseng, Benjamin M; Parker, Rosemary; Riley, Jonathan; Tinajero, Cynthia; Zhang, Rong
Blood ejected from the left ventricle perfuses the brain via central elastic arteries, which stiffen with advancing age and may elevate the risk of end-organ damage. The purpose of this study was to determine the impact of central arterial aging on cerebral hemodynamics. Eighty-three healthy participants aged 22 to 80 years underwent the measurements of cerebral blood flow (CBF) and CBF velocity (CBFV) using magnetic resonance imaging (MRI) and transcranial Doppler, respectively. The CBF pulsatility was determined by the relative amplitude of CBFV to the mean value (CBFV%). Central arterial stiffness (carotid-femoral pulse wave velocity), wave reflection (carotid augmentation index), and pressure were measured using applanation tonometry. Total volume of white-matter hyperintensity (WMH) was quantified from MR images. Total CBF decreased with age while systolic and pulsatile CBFV% increased and diastolic CBFV% decreased. Women showed greater total CBF and lower cerebrovascular resistance than men. Diastolic CBFV% was lower in women than in men. Age- and sex-related differences in CBF pulsatility were independently associated with carotid pulse pressure and arterial wave reflection. In older participants, higher pulsatility of CBF was associated with the greater total volume of WMH. These findings indicate that central arterial aging has an important role in age-related differences in cerebral hemodynamics.